INTERVENSI CYTOADHERENCE SEBAGAI PELUANG UNTUK PENCEGAHAN DAN TERAPI MALARIA BERAT - Simamora, Dorta; Sumitro, Sutiman B.; Fitri, Loeki Enggar (Fakultas Kedokteran Universitas Brawijaya, 2006)
Abstract In malarial infection, erythrocytes infected wih Plasmodium falciparum bind to endothelial vascular (endothelial cytoadherence). This binding is implicated in the forming of sequestre and rosette that affects the vascular circulation, and thus injures the capillary wall. This mechanism is important in pathogenesis of malarial due to dysfunction of several organs. There are several receptors of cytoadherence in human e.g Thrombospondine (TSP), CD-36, ICAM-1, and ELAM-1 as well as specific ligands of the parasite e.g Plasmodium falciparum Erythrocyte Membrane Protein-1 (PfEMP-1), 220 kDa protein of Pf60, Pf332, sequestrin, Pfaldhesin and STEVOR. PfEMP-1 has been revealed as a molecule that is responsible for pathogenesis of severe malaria. This protein can pass parasitophorous vacoular membrane (PVM) of the parasite by attaching its molecule to carry Protein Export Elemen (PEXEL) and than go to the surface of erythrocytes in combination with specific helper protein in maeurer cleft. The intervention on cytoadherence process through blocking of specific ligand directly or blocking the translocation of this ligand to the surface of erythrocytes might be important in regulating the outcome of malarial infection. Key words : Cytoadherence, severe malaria, intervention, adhesion molecule.